PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPA KELAS V SDN 42 PONTIANAK KOTA - Martini, Sri; Kresnadi, Hery; Uliya, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe influence of the use of model problem based learning on the learning results of class IPA V. This study aims to describe how much influence the use of model problem based learning on the results of IPA learning. The method used in this research is experimental method. Form of Quasi Experimental research forms non-equivalent control group design experiments design. Data collection techniques is a measurement technique. Based on statistical calculation average learning result of post-test of control class equal to 61,3 and experiment class post-test equal to 70,83. Hypothesis test results (t-test) obtained t_hitung = 2,84 for dk = 58 and α = 5% obtained t_tabel = (2,0021) which means t_hitung (2,84)> t_table (2,0021), then Ha received. From the calculation of effect size (ES) obtained ES of 0,82 the category Large. From the Explanation then, it can be concluded that there is influence of the model problem based learning on the results of study IPA class V State Elementary School A District Pontianak City.Keywords: Influence, Model Problem Based Learning, Learning                     Outcomes